Eksistensi Perkawinan Adat Jawa Di Desa Kalibalangan Kecamatan Abung Selatan Kabupaten Lampung Utara - Misgiharjo Alias Gigih; Irawan Suntoro; Mona adha (FKIP Unila, 2023)
This study aims to explain and describe the existence of Javanese traditional marriage in Kalibalangan Village, Abung Selatan District, Lampung Utara Regency. The research method used in this research is a descriptive qualitative approach with the research subjects, namely traditional leaders, community leaders, youth leaders, families who are married, and married couples. The data collection techniques used interviews, observation, and documentation, while the validity of the data used credibility and triangulation tests. Based on the results of the research, it shows that most people carry out traditional Javanese marriages with the motivation to preserve the existing culture, show their Javanese identity, to be respected, get support, show that they can carry out traditional Javanese marriages, get satisfaction. Then there are values contained in the five stages of the Javanese traditional marriage procession, these values are supported by human values such as cooperation, helping fellow communities, the value of unity among communities with harmonious relationships among people and solidarity among communities as part of citizens. the divine value that exists in the community by expecting the blessing of the event, the smooth running of the program from God Almighty. Meanwhile, the challenge to efforts to carry out marriage with Javanese customs in the present is to continue to carry out Javanese traditional marriages, and to simplify the process to save time in implementing these Javanese customs.Keywords: Existence of Traditional, Javanese Marriage, Lampung, Traditional